Mandarin–Italian Dual-Language Children’s Comprehension of Head-Final and Head-Initial Relative Clauses - Hu, Shenai; Costa, Francesca; Guasti, Maria Teresa (Frontiers in Psychology, 2020)
The acquisition of languages by children using two languages is a matter of debate as many factors contribute to the success of this type of acquisition. We focus on how the competence of dual-language children changes in their two languages as a function of length of exposure and establish whether there are reciprocal influences during language development. We examined the comprehension of subject and object relative clauses in a group of 6-year-old (younger) and 8-year-old (older) Mandarin–Italian dual-language children. After 3 years of regular and intensive exposure to Italian, the younger group reached the same level of competence in the comprehension of relative clauses in their two languages, and after 5 years of exposure to Italian, the older group had a better comprehension of relative clauses in Italian than in Mandarin. Acquiring two languages leads to bidirectional influence, beyond a reciprocal support. Finally, some penalty may be observed in the acquisition of subject head-final relative clauses, which is not evident in that of subject head-initial relative clauses.